2019
DOI: 10.1249/mss.0000000000001765
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Midfoot in Drop Landings

Abstract: Kinematic data revealed an average sagittal plane midtarsal joint range of motion (ROM) of 27 degrees through the landing phase. Kinetic data showed that between 7% and 22% of the total lower extremity joint work during the landing was performed by the midtarsal joint. Both standing AHI and static midtarsal joint angle (static MA) were correlated with sagittal plane midtarsal joint ROM (standing AHI: r=-0.320, p=0.026; static MA: r=0.483, p<0.001) and with midtarsal joint work (standing AHI: r=0.332, p=0.021; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
2
8
1
Order By: Relevance
“…Contrary to our second hypothesis, we observed no plateau in negative foot work contributions as the energy dissipation requirements increased. Our results are similar to those of Olsen et al (2019), who reported mid-foot energy dissipation during drop landings (0.4 m) and found that between 8% and 11% of the COM work during landing was performed about the mid-foot (Olsen et al, 2019). Our data suggest that ∼18% of the total COM negative work is performed at the foot during deceleration tasks.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Contrary to our second hypothesis, we observed no plateau in negative foot work contributions as the energy dissipation requirements increased. Our results are similar to those of Olsen et al (2019), who reported mid-foot energy dissipation during drop landings (0.4 m) and found that between 8% and 11% of the COM work during landing was performed about the mid-foot (Olsen et al, 2019). Our data suggest that ∼18% of the total COM negative work is performed at the foot during deceleration tasks.…”
Section: Discussionsupporting
confidence: 90%
“…Because of the relatively small physiological cross-sectional area of the intrinsic foot muscles, their force generating and, thereby, energetic contributions may be limited, especially as COM energy demands increase (Farris et al, 2019;Riddick et al, 2019). A recent study by Olsen et al (2019) provides some insight that the foot can contribute to energy dissipation during rapid deceleration tasks. They reported ∼11% of the total lower-body energy dissipation during drop landings from 0.4 m was performed about the mid-tarsal joint of the foot (Olsen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olsen et al [ 21 ] reported the kinematic characteristics of the metatarsophalangeal (MTP) joint during forward drop landing. At the moment of ground contact, the first MTP joint was rapidly extended to 20°.…”
Section: Discussionmentioning
confidence: 99%
“…Across walking, running and drop landing, the foot can contribute up to 22% of the total lower limb joint work (Arch and Fylstra, 2016;Olsen et al, 2019;Zelik et al, 2015). A previous study has reported that a reduction in distal ankle loading resulted in a compensatory increase in proximal knee loading during cutting (Wannop et al, 2014).…”
Section: Introductionmentioning
confidence: 99%